Penggunaan Metode Simple Additive Weighting dalam Sistem Pendukung Keputusan Evaluasi Potensi Pegawai di SMK Negeri 2 Bandar Lampung - Rizky Ramadhany; Machudor Yusman; Anie Rose Irawati; Akmal Junaidi (Jurnal Pepadun, 2023)
This research was conducted to build a decision support system for employee potential assessment at SMK Negeri 2 Bandar Lampung using the Simple Additive Weighting (SAW) method. Decision support system is made web based with 3 actors namely admin, employees and leaders. The data used comes from the Employee Work Target (SKP) data at SMK Negeri 2 Bandar Lampung. The selection process is done by collecting employee data and employee performance values along with the criteria used. The data received is processed by the system by determining the priority of each criterion and doing the sum of the weights of each criterion value. The results of functional testing in the SPK Employee Potential Assessment is a compatible system on the computer being tested and all menus on the system are running well. The results of testing the system using Black Box Testing using 20 data employees of SMK Negeri 2 Bandar Lampung. The conclusion of this research is that the Employee Potential Assessment Decision Support System can help the Head of SMK Negeri 2 Bandar Lampung to conduct a performance evaluation of employees with 100% accuracy. Thus, the SAW method is appropriately used in the Employee Potential Assessment Decision Support System.